1997
DOI: 10.1007/bf02430678
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of enzyme-containing cellulose fibre materials from graft copolymers containing sulfo groups

Abstract: An analysis of the experimental data and their comparison with previously published [3] results led to the following conclusions: the rate of interpolymer reactions (IPR) involving lysozyme (LYS) and cellulose graft copolymer containing strongly acid groups (sulfo groups) is much lower than the rate of the reaction betweenChemical addition of enzymes to polymers containing ionizable groups makes it possible to create biologically active materials [1, 2]. The systematic study of the characteristics of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…for their modification. Our data [4][5][6][7][8] showed that when graft copolymers of cellulose containing ionogenic groups are used for immobilization of enzymes, the required properties are basically obtained by altering the type, concentration, and localization of the ionogenic groups in the structure of the fibre. For unmodified fibre materials, this problem could be solved by using polymer matrices of varying structure, composites of different composition which include polysaccharides and their derivatives containing ionogenic groups in addition to biologically active substances, water-soluble synthetic polymers, and polyfunctional low-molecular-weight reagents [9][10][11][12][13].…”
mentioning
confidence: 98%
“…for their modification. Our data [4][5][6][7][8] showed that when graft copolymers of cellulose containing ionogenic groups are used for immobilization of enzymes, the required properties are basically obtained by altering the type, concentration, and localization of the ionogenic groups in the structure of the fibre. For unmodified fibre materials, this problem could be solved by using polymer matrices of varying structure, composites of different composition which include polysaccharides and their derivatives containing ionogenic groups in addition to biologically active substances, water-soluble synthetic polymers, and polyfunctional low-molecular-weight reagents [9][10][11][12][13].…”
mentioning
confidence: 98%